Efektifitas Pemanfaatan Laporan Pajak Elektronik di Wilayah Kantor Pelayanan Pajak (KPP) Pratama Jakarta Pluit - Jakarta Utara - Baharuddin Saga; Wizanasari Wizanasari (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2021)
This study presents the results of a qualitative study on the implementation of electronic tax reporting by taxpayers registered in KPP Pratama Jakarta Pluit, namely qualitative research with data collection methods using in-depth interviews with related parties such as taxpayers, also experts in the field being studied. Data collection is also carried out by means of a Group Discussion Forum (FGD) to determine the level of taxpayer compliance in electronic tax reporting, as well as finding the right solution to be able to use electronic tax reporting for taxpayers. All respondents in this study revealed that electronic tax reports are very helpful for taxpayers in the submission process of tax reports and are very efficient both in time and cost, but the ability of taxpayers to use electronics still needs guidance, even though all legal umbrellas have been made in such a way, especially for entrepreneurs. the “small” who incur high costs for this.